Optimism’s Explicative Role for Chronic Diseases - Avvenuti, Giulia; Baiardini, Ilaria; Giardini, Anna (Frontiers in Psychology, 2016)
The increasing interest about dispositional optimism's role in health status and its positive modulating effect on health outcomes has led to a remarkable scientific production in the last decade. To date lot is known about which fields of medicine are affected by optimism, instead much less is known about how optimism interacts with other factors, both biological and psychological, in determining health status. The aim of this mini review is to explore the literature derived from clinical and experimental research assessing the associations between dispositional optimism and health status. Dispositional optimism can be considered as facet of personality that is cognitive in nature which holds the global expectation that the future will be plenty of good events. Optimists view desired goals as obtainable, so they often confront adversities in active manners resulting in perseverance and increased goal attainment. Only studies that explicitly included optimism and health outcomes, as measurable variables, and that reported a clear association between them have been reviewed. Cancer, cardiovascular disease, respiratory failure and ageing with multimorbidity were considered. Among the possible explicative hypotheses, two seem to best describe results: optimism may have a direct effect on the neuroendocrine system and on immune responses, and it may have an indirect effect on health outcomes by promoting protective health behaviors, adaptive coping strategies and enhancing positive mood. The research on optimism and health status has already shed light on important mechanisms regarding chronic diseases' management, however further studies are needed to deepen the knowledge.